A Detailed Analysis of Parameters Supporting the Engraftment and Growth of Chronic Lymphocytic Leukemia Cells in Immune-Deficient Mice - Patten, Piers E. M.; Ferrer, Gerardo; Chen, Shih-Shih; Kolitz, Jonathan E.; Rai, Kanti R.; Allen, Steven L.; Barrientos, Jacqueline C.; Ioannou, Nikolaos; Ramsay, Alan G.; Chiorazzi, Nicholas (Frontiers in Immunology, 2021)
Patient-derived xenograft models of chronic lymphocytic leukemia (CLL) can be created using highly immunodeficient animals, allowing analysis of primary tumor cells in an in vivo setting. However, unlike many other tumors, CLL B lymphocytes do not reproducibly grow in xenografts without manipulation, proliferating only when there is concomitant expansion of T cells. Here we show that in vitro pre-activation of CLL-derived T lymphocytes allows for a reliable and robust system for primary CLL cell growth within a fully autologous system that uses small numbers of cells and does not require pre-conditioning. In this system, growth of normal T and leukemic B cells follows four distinct temporal phases, each with characteristic blood and tissue findings. Phase 1 constitutes a period during which resting CLL B cells predominate, with cells aggregating at perivascular areas most often in the spleen. In Phase 2, T cells expand and provide T-cell help to promote B-cell division and growth. Expansion of CLL B and T cells persists in Phase 3, although some leukemic B cells undergo differentiation to more mature B-lineage cells (plasmablasts and plasma cells). By Phase 4, CLL B cells are for the most part lost with only T cells remaining. The required B-T cell interactions are not dependent on other human hematopoietic cells nor on murine macrophages or follicular dendritic cells, which appear to be relatively excluded from the perivascular lymphoid aggregates. Notably, the growth kinetics and degree of anatomic localization of CLL B and T cells is significantly influenced by intravenous versus intraperitoneal administration. Importantly, B cells delivered by the intraperitoneally either remain within the peritoneal cavity in a quiescent state, despite the presence of dividing T cells, or migrate to lymphoid tissues where they actively divide; this dichotomy mimics the human condition in that cells in primary lymphoid tissues and the blood are predominately resting, whereas those in secondary lymphoid tissues proliferate. Finally, the utility of this approach is illustrated by documenting the effects of a bispecific antibody reactive with B and T cells. Collectively, our model represents a powerful tool to evaluate CLL biology and novel therapeutics in vivo.